The Effect Of Kap Size, Audit Tenure, And Audit Industry Specialization On Earnings Management (Empirical Study On Manufacturing Companies Listed On The Indonesia Stock Exchange - Fadma Alnadhira Sembiring; Muhammad Fahmi (Proceeding International Seminar of Islamic Studies, 2019)
The purpose of this study is to examine and analyze the effect of KAP size, audit tenure, and audit industry specialization on earnings management in manufacturing companies listed on the Indonesia Stock Exchange. This research approach is associative. The object of this research is a manufacturing company listed on the Indonesia Stock Exchange in 2013-2017. So that the sample obtained is 150 financial statements of manufacturing companies listed on the Indonesia Stock Exchange. The data used is external data obtained from the Jalan IDX office. Ir. H. Juanda Baru No. A5-A6, Medanda collected will be analyzed using the data analysis method, first testing the classical assumptions before testing the hypothesis. Hypothesis testing in this study used multiple linear regression with t test, F test and coefficient of determination test which was carried out with the help of the SPSS computer program. Based on the results of this study indicate that the size of KAP has an effect on to earnings management partially. And simultaneously the size of KAP, audit tenure and audit industry specialization have an effect on earnings management.